2023
DOI: 10.1371/journal.pone.0282159
|View full text |Cite
|
Sign up to set email alerts
|

Visual recognition and prediction analysis of China’s real estate index and stock trend based on CNN-LSTM algorithm optimized by neural networks

Abstract: Today, with the rapid growth of Internet technology, the changing trend of real estate finance has brought great an impact on the progress of the social economy. In order to explore the visual identification (VI) effect of Convolutional Neural Network and Long Short-Term Memory (CNN-LSTM) algorithm based on neural network optimization on China’s real estate index and stock trend, in this study, artificial neural network (ANN) algorithm is introduced to predict its trend. Firstly, LSTM algorithm can effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In general, formatting nulls, filtering out null values, normalizing the data, visualizing the data, and performing correlation analysis all contribute to preparing the dataset for further analysis. This makes the dataset more appropriate for generating relevant insights and drawing correct conclusions [26][27][28][29][30][31][32].…”
Section: Spo2mentioning
confidence: 99%
“…In general, formatting nulls, filtering out null values, normalizing the data, visualizing the data, and performing correlation analysis all contribute to preparing the dataset for further analysis. This makes the dataset more appropriate for generating relevant insights and drawing correct conclusions [26][27][28][29][30][31][32].…”
Section: Spo2mentioning
confidence: 99%
“…Zhou [16] found that the deep-learning model CNN-LSTM has a strong learning ability and overfitting resistance to nonlinear relationships. Lu et al [17] and Chen [18] utilized the CNN-LSTM model for stock price prediction and found that the model prediction accuracy was higher. However, CNN-LSTM models in the existing literature mainly focus on stock price trend prediction and less on the prediction of stock price volatility.…”
Section: Introductionmentioning
confidence: 99%